Innovative Issues in Intelligent Systems - Sgurev, Vassil; Yager, Ronald R.; Kacprzyk, Janusz; Jotsov, Vladimir (Studies in Computational Intelligence, 2016)
This book presents a broad variety of different contemporary IT methods and applications in Intelligent Systems is displayed. Every book chapter represents a detailed, specific, far reaching and original re-search in a respective scientific and practical field. However, all of the chapters share the common point of strong similarity in a sense of being innovative, applicable and mutually compatible with each other. In other words, the methods from the different chapters can be viewed as bricks for building the next generation "thinking machines" as well as for other futuristic logical applications that are rapidly changing our world nowadays.